2017
DOI: 10.15761/vrr.1000129
|View full text |Cite
|
Sign up to set email alerts
|

Larvicidal and ovicidal activities, characterization and stability of Anacardium occidentale (Cashew) shell wastes

Abstract: Dengue and zika continue to be the most rapidly emerging febrile diseases and pose a negative impact on social and economic activity of the country. Despite of recent innovation in dengue vaccine, eradication of the vector, Aedes aegypti, is still the best way to inhibit dengue and zika outbreaks. In this study, we evaluated the larvicidal and ovicidal activities and characterized the shell wastes of Anacardium occidentale including its stability for a period of two (2) years. The shell wastes were extracted u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…showed the highest larvicidal activities with LC 50 of 4.01 mg/L and LC 90 of 11.29 mg/L compared to the commercial larvicide [28]. Anacardic acid in cashew methanol extract was larvicidal in both Ae.…”
Section: Field Evaluation Results Of Larvicidal Effect Of Apl Formulationmentioning
confidence: 94%
See 2 more Smart Citations
“…showed the highest larvicidal activities with LC 50 of 4.01 mg/L and LC 90 of 11.29 mg/L compared to the commercial larvicide [28]. Anacardic acid in cashew methanol extract was larvicidal in both Ae.…”
Section: Field Evaluation Results Of Larvicidal Effect Of Apl Formulationmentioning
confidence: 94%
“…Egg hatching inhibitory activities of the cashew nut shell liquid extract against Ae. aegypti, which contains anacardic acid, showed LC 50 of 8.06 mg/L and LC 90 of 15.53 mg/L [28]. Nevertheless, Hebeish suggested that the mosquito repellent effect improved as concentration and duration of exposure to limonene increased [43].…”
Section: Field Evaluation Results Of Larvicidal Effect Of Apl Formulationmentioning
confidence: 99%
See 1 more Smart Citation